Secreted proteases from pathogenic fungi - Monod, M.; Capoccia, S.; Lechenne, B.; Zaugg, C.; Holdom, M.; Jousson, O.
Manyspecies of human pathogenic fungi secrete proteases in vitro or during the infection process. Secreted endoproteases belong to the aspartic proteases of the pepsin family, serine proteases of the subtilisin family, and metalloproteases of two different families. To these proteases has to be added the non-pepsin-type aspartic protease from Aspergillus niger and a unique chymotrypsin-like protease from Coccidioides immitis. Pathogenic fungi also secrete aminopeptidases, carboxypeptidases and dipeptidyl-peptidases. The function of fungal secreted proteases and their importance in infections vary. It is evident that secreted proteases are important for the virulence of dermatophytes since these fungi grow exclusivelyin the stratum corneum, nails or hair, which constitutes their sole nitrogen and carbon sources. The aspartic proteases secreted by Candida albicans are involved in the adherence process and penetration of tissues, and in interactions with the immune system of the infected host. For Aspergillus fumigatus, the role of proteolytic activity has not yet been proved. Although the secreted proteases have been intensivelyinvestigated as potential virulence factors, knowledge on protease substrate specificities is rather poor and few studies have focused on the research of inhibitors. Knowledge of substrate specificities will increase our understanding about the action of each protease secreted bypathogenic fungi and will help to determine their contribution to virulence.
Keywords: PROTEASES; VIRULENCE; CANDIDA; ASPERGILLUS; DERMATOPHYTES; ADHERENCE